Nexus between Financial Development and Income Inequality before Pandemic Covid-19: Does Financial Kuznets Curve Exist in Malaysia, Indonesia, Thailand and Philippines? - Ridzuan, Abdul Rahim; Zakaria, Shahsuzan; Fianto, Bayu Arie; Yusoff, Nora Yusma Mohamed; Sulaiman, Nor Fatimah Che; Razak, Mohamad Idham Md; Siswantini, Siswantini; Lestari, Arsiyanti (International Journal of Energy Economics and Policy, 2021)
This study offers new insights for policymakers to reduce income inequality, thus ensuring economic growth which greatly benefits the poor segment of population and directing financial sector to provide easy access to financial resources for lower income group at cheaper cost. Bound test was applied to examine the long-run and short-run relationships based on the sample period beginning from 1970 until 2016. The results confirmed the existence of a long-run relationship between the variables. Financial development in Malaysia, Indonesia and Thailand had successfully reduced income inequality, however, a different effect was recorded in the Philippines where income distribution was worsened. Furthermore, economic growth brought positive effect to income distribution in Malaysia and Indonesia, but not for Thailand and the Philippines. Inflation, trade openness and foreign direct investment, provided mixed results for all countries. Among the policies recommendation for this paper are there should be more easy accessibility for entrepreneurs to reach the wide range of financial services including conventional and Islamic financial products, the expansion of capital market, as well as giving proper attention to the financial sector. Besides, granting the access to capital markets for low income groups or underprivileged individuals might be helpful to them either by developing entrepreneurial skill or involvement in productive activities and receive better salaries. This policies will gives insight to the policymakers as it the outcome is based on the spread of pandemic Covid-19 that hit the world. Keywords: Financial Development; Income Inequality; ASEAN-4; Financial Kuznets Curve JEL Classifications: G10; F62 DOI: https://doi.org/10.32479/ijeep.10616